How 'should' the majority group acculturate? Acculturation expectations and their correlates among minority- and majority-group members. (March 2023) - Kunst, Jonas R.; Ozer, Simon; Lefringhausen, Katharina; Bierwiaczonek, Kinga; Obaidi, Milan; Sam, David L.
Abstract: Do minority-group members welcome or reject that majority-group members adopt other cultures? Acculturation is commonly defined as a process of mutual accommodation. Yet, the acculturation of majority-group members has only recently received research attention. To date, we do not know the extent to which minority-group members expect majority-group members to adopt the culture of minority groups and/or to maintain their mainstream culture. Knowledge is also lacking about how these expectations relate to minority-group members' own acculturation orientations and symbolic and realistic threat perceptions. We further do not know whether such associations are similar among minority- and majority-group members. To address these gaps, we surveyed 246 Muslim minority-group members and 247 White Christian majority-group members in the United Kingdom. Muslim minority-group members' acculturation expectations towards majority-group members were normally distributed around the midpoint of the scale, suggesting that they did not reject majority-group acculturation on average. Acculturation expectations were correlated with symbolic and realistic threat perceptions among majority-group members but not among minority-group members. Cluster analyses showed that integrated Muslim minority-group members found it relatively important for majority-group members to adopt minority-group culture and to maintain their own culture. In sum, the results support the idea that minority-group members, at least in some contexts and settings, view acculturation as a mutual cultural change rather than as cultural appropriation.